Efektifitas Media Sosial Youtube Modifikasi Teka Teki Silang Dalam Edukasi Kesehatan Gigi dan Mulut Pada Siswa - Siswi SDN 015 Sungai Sirih - Jeffry Kurniawan; Oktavia Dewi; Emy Leonita; Nurlisis Nurlisis; Irwan Muryanto (Jurnal Kesehatan Komunitas, 2021)
The majority of Indonesian suffers from oral and dental disease specifically dental supporting tissue and tooth caries due to the neglect of oral hygiene. Based on data about the number of patched tooth done to elementary student of 015 Sungai Sirih there are 61% caries index by Public Health Center of Sungai Sirih. Behavior and formal education plays important role since oral and dental health is affected as the result of certain behavior.Â  The purpose of this research is to know the effectiveness of youtube modification in crossword puzzle to student's knowledge in Elementary School 015 Sungai Sirih. This research is quantitative based using Quasi Experiment - Nonequivalent Control Design. It is consisted of 54 students of fifth grade. Respondents fill out questionnaires, pre-test, and post-test, and collected as primary data. Analysis applied in this research is Wilcoxon and Kruskal Wallis analysis. In terms of knowledge, with original crossword puzzle it has flattened a mean is 24.72 Mean. However, youtube modified crossword puzzle the number increased to mean is 79.94. From this study it can be concluded that youtube modified crossword puzzle is considered to be more effective attempt to enhance student's knowledge about oral and dental health in Elementary Schools 015 Sungai Sirih with category knowledge increase to 100 % Conclusion is youtube modified crossword puzzle giving effect to information oral health.